Myocardial infarction with non obstructive coronary arteries (MINOCA): a whole new ball game. (2nd January 2017) - Poku, Nana; Noble, Stephane
ABSTRACT: Introduction : MINOCA is a clinical syndrome that encompasses a subgroup of heterogeneous patients who present with myocardial infarction yet do not have any significant coronary artery obstruction on angiogram. As many as one in ten patients with acute myocardial infarction (AMI) will not have an occluded coronary artery, and the reported prevalence keeps rising, in part due to better recognition of this syndrome. Current guidelines offer several diagnostic algorithms but MINOCA remains largely under-recognised and little is known about whether patients might benefit from a more specific treatment modality. Areas covered : We review pathogenesis, diagnosis, prognosis, and management of MINOCA. Expert commentary : Due to the significant heterogeneity of MINOCA patients, a more efficient management strategy may solely rely on an individualized approach in order to improve outcomes.